Undecilenic acid of mamone oil as antisseptic in dogs - Marinho, Allysson Vinícius Benevides; Alves, Nilza Dutra; Feijó, Francisco Marlon Carneiro; Rodrigues, Gardênia Silvana de Oliveira; Santos, Caio Sérgio; Sant’Anna, Andrea (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The present study aimed to evaluate the possibility of using undecylenic acid, extracted from castor oil (Ricinus communis), as an antiseptic in dogs (Canis lupus familiaris). For this purpose, a prototype of a treadmill, made of castor resin, covered with an acid impregnated adhesive mat, on which the animals of the study were walked, was used. The work was developed with 54 dogs and the samples of the swabs of the cushions were collected from the right (control) and left (test) anterior limbs, and the control and test samples were collected, respectively, before and after the use of the treadmill. After the collection, the swabs were packaged in isothermal boxes with recyclable ice and sent for processing in the Laboratory of Veterinary Microbiology. After incubation at 37ºC for 24 to 48 hours, the individual counts of each CFU / ml plate were performed, the results were obtained from the means of the duplicates for each dilution and organized into tables and figures. Of the 54 animals, 81.48% presented a reduction of the microbial population, 14.81% presented absence of variation of the microbial population and 3.70% presented increase of the microbial population. Considering only the viable results, 95,65% presented a reduction of the microbial population, therefore it can be concluded that the undecylenic acid has an antiseptic action, considerably reducing the population of microorganisms present in dogs’ cushions.